Steel Fibre Reinforced Concrete Meso-Scale Numerical Analysis - Zhengwei Li; Meizhong Wu; Jiawei Wu; Yujun Cui; Xingwei Xue (Advances in Civil Engineering)
Concrete is a heterogeneous composite consisting of aggregate, cement paste, and void. Steel fibre reinforced concrete (SFRC) has been widely studied experimentally and numerically in recent decades. The fibre geometry model program generated by a secondary development ANSYS program was exported to midas FEA for analysis. The constitutive concrete model adopts the total strain crack model of concrete. A steel fibre bond slip is considered in an equivalent manner using the von Mises model. The results of the three-dimensional meso-scale numerical analysis method agree well with the experimental values of steel fibre concrete beams.